2012
DOI: 10.1016/j.gaitpost.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry-based gait analysis, an additional objective approach to screen subjects at risk for falling

Abstract: This study investigated whether the Tinetti scale, as a subjective measure for fall risk, is associated with objectively measured gait characteristics. It is studied whether gait parameters are different for groups that are stratified for fall risk using the Tinetti scale. Moreover, the discriminative power of gait parameters to classify elderly according to the Tinetti scale is investigated. Gait of 50 elderly with a Tinneti>24 and 50 elderly with a Tinetti≤24 was analyzed using acceleration-based gait analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 30 publications
5
87
0
9
Order By: Relevance
“…The common walking tests performed in clinics on subjects with amputation, such as the 10 m walking test or the 6 min walking test [45], just measure speed of walking without providing information about the optimization of other important aspects of gait. Our study also showed that fast speed may not be a safe choice, because it may lead to less harmonic gait, exposing subjects to a higher risk of falling [17,38].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The common walking tests performed in clinics on subjects with amputation, such as the 10 m walking test or the 6 min walking test [45], just measure speed of walking without providing information about the optimization of other important aspects of gait. Our study also showed that fast speed may not be a safe choice, because it may lead to less harmonic gait, exposing subjects to a higher risk of falling [17,38].…”
Section: Discussionmentioning
confidence: 69%
“…In the literature, the expression "gait stability" has been used with reference to the ability to walk with smoothed upper-body accelerations [13], as well as stride-to-stride kinematic variability [14] and local dynamic stability related to the ability of the locomotor system to maintain continuous motion by accommodating natural, infinitesimally small perturbations [15]. Although mathematically and conceptually different, all of these parameters have been found related to balance and risk of falling [14,[16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The use of inertial sensors to help clinicians to assess the risk of fall has been widely studied [9], [22]- [24]. These systems generally derive a model to classify users as fallers or non-fallers, on the basis of some relevant gait parameters.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…25 Half of the females had a walking speed of less than 0.7 m/s at F4, suggesting safety problems in traffic environments as well as an increased risk to fall. 26 All participants improved TUG from their baseline level but only 33% of the females and 64% of the males were able to perform TUG at F4 within the mid-reference time of 11.3 seconds for elderly people aged 80 to 99. 12 Only 45% of females and 64% of males were able to perform more than 5 chair stands in 30 seconds at F4 representing increased risk of falling and indicating the frailty of the assessed group.…”
Section: General Motor Function (Not Shown)mentioning
confidence: 84%